COVID-19–Related Fatalities and Intensive-Care-Unit Admissions by Age Groups in Europe: A Meta-Analysis - Cohen, Jérémie F.; Korevaar, Daniël A.; Matczak, Soraya; Chalumeau, Martin; Allali, Slimane; Toubiana, Julie (Frontiers in Medicine, 2021)
Objectives: Precise international estimates of the age-breakdown of COVID-19-related deaths and intensive care unit (ICU) admissions are lacking. We evaluated the distribution of COVID-19-related fatalities and ICU admissions by age groups in Europe. Materials and Methods: On April 6, 2020, we systematically reviewed official COVID-19-related data from 32 European countries. We included countries that provided data regarding more than 10 COVID-19-related deaths stratified by age according to pre-specified groups (i.e., < 40, 40-69, ≥ 70 years). We used random-effects meta-analysis to summarize the data. Results: Thirteen European countries were included in the review, for a total of 31,864 COVID-19-related deaths (range: 27-14,381 per country). In the main meta-analysis (including data from Germany, Hungary, Italy, Netherlands, Portugal, Spain, Switerland; 21,522 COVID-19-related fatalities), the summary proportions of persons < 40, 40-69, and ≥ 70 years of age among all COVID-19-related deaths were 0.1% (0.0-0.2%; I2 28.6%), 13.0% (10.8-15.4%; I2 91.5%), and 86.6% (84.2-88.9%; I2 91.5%), respectively. ICU data were available for 4 countries (France, Greece, Spain, Sweden). The summary proportions of persons around < 40-50, around 40-69, and around ≥ 60-70 years of age among all COVID-19-related ICU admissions were 5.4% (3.4-7.8%; I2 89.0%), 52.6% (41.8-63.3; I2 98.1%), and 41.8% (32.0-51.9%; I2 99%), respectively. Conclusions: People under 40 years old represent a small fraction of most severe COVID-19 cases in Europe. These results may help health authorities respond to public concerns and guide future physical distancing and mitigation strategies. Specific measures to protect the elderly should be considered.